Anti-inflammatory Therapy for Coronary Atherosclerotic Heart Disease: Unanswered Questions Behind Existing Successes - Ma, Jun; Chen, Xiaoping (Frontiers in Cardiovascular Medicine, 2021)
Coronary atherosclerotic heart disease is a serious threat to human health. The results of the Canakinumab Anti-Inflammatory Thrombosis Outcome Study published in 2017 put an end to the perennial debate about the anti-inflammatory treatment of coronary atherosclerotic heart disease. In addition to interleukin 1β monoclonal antibody, interleukin 6 receptor antagonists and colchicine have also shown exciting results in clinical trials within the last 3 years. However, behind these successes, questions remain that need to be addressed. In this review, we summarize the successes and existing doubts of interleukin 1β antibodies, interleukin 6 receptor antagonists, and colchicine in the anti-inflammatory treatment of coronary atherosclerotic heart disease.